Implementasi E-Order Dalam Peningkatan Pengadaan Barang Dan Jasa Di Sekretariat Kota Administrasi Jakarta Pusat Tahun 2022 - Widiastuti, Yuni (CV RIFAINSTITUT, 2023)
The focus of this research is the implementation of E-Order in improving the procurement of goods and services in the Secretariat of Central Jakarta City Administration in 2022. E-order implementation is part of the e-procurement at the DKI Jakarta Provincial government. In the Secretariat of Central Jakarta City Administration, the goods and services are procured through e-order by the existing departments within the Secretariat of Central Jakarta City Administration, including in its Urban Villages and Sub Districts. However, the components for the goods and service procurements through e-order are currently still limited. The purpose of this research is to analyze and evaluate the implementation of E-Order in the procurement of goods and services in the Secretariat of Central Jakarta City Administration in 2022. In addition, the study examined the obstacles encountered during its implementation and the measures taken to overcome them. The research utilized a qualitative descriptive method, whereby the results were based on the analysis of interview data, field observations, and desk study. There were five informants participated in the interview. Based on the research findings, implementing E-Order in the procurement of goods and services has been effective in terms of bureaucracy structure, resources, communication, and disposition. However, there is a need to improve other resources, such as information technology, facilities, and infrastructure, to support the implementation of E-Order.